2018
DOI: 10.1038/s41598-018-35468-3
|View full text |Cite
|
Sign up to set email alerts
|

Diffracted X-ray Blinking Tracks Single Protein Motions

Abstract: Single molecule dynamics studies have begun to use quantum probes. Single particle analysis using cryo-transmission electron microscopy has dramatically improved the resolution when studying protein structures and is shifting towards molecular motion observations. X-ray free-electron lasers are also being explored as routes for determining single molecule structures of biological entities. Here, we propose a new X-ray single molecule technology that allows observation of molecular internal motion over long tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
(27 reference statements)
0
25
0
Order By: Relevance
“…Our DXB analysis, without the tracking of diffraction spots, analyses the time-resolved fluctuations of the diffraction intensity using the ACF. Our previous study showed that the ACF decay constant of protein molecules with nanocrystals correlates with the angular velocity 12 . The time trajectory of the diffraction intensity of silver halides reflects the grain motions during the photolysis chemical reaction.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Our DXB analysis, without the tracking of diffraction spots, analyses the time-resolved fluctuations of the diffraction intensity using the ACF. Our previous study showed that the ACF decay constant of protein molecules with nanocrystals correlates with the angular velocity 12 . The time trajectory of the diffraction intensity of silver halides reflects the grain motions during the photolysis chemical reaction.…”
Section: Resultsmentioning
confidence: 96%
“…S3 ). The time-resolved intensity fluctuation of each pixel was computed to evaluate rotational motions using the following autocorrelation function (ACF) 12 : where I(t) represents the diffracted photon intensity. The brackets 〈〉 indicate time-averaged values.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DXT refers to the technique of labeling specific sites of protein molecules with gold nanocrystals and monitoring their local movements by tracking the diffraction spots from the nanocrystals. Previously, intense X-ray beams were required for these measurements, but recently Sekiguchi has developed a technique with much lower doses of X-ray, by observing the diffracted intensity fluctuation from the nanocrystals (Sekiguchi et al 2018).…”
mentioning
confidence: 99%